2022
DOI: 10.3389/fonc.2022.855546
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Outcomes in Female Patients With Ileal Conduit or Orthotopic Neobladder Urinary Diversion: 6-Month Results of a Multicenter Prospective Study

Abstract: Radical cystectomy (RC) often affects patients’ life as this surgery is a traumatic and invasive event for the patients, with drawbacks on their daily, social, working, and sex life. Such changes in the quality of life (QoL) of patients are commonly studied through retrospective clinical evaluations and rarely with longitudinal studies. To date, studies focusing on functional outcomes, sexual function, and health-related QoL for female patients are lacking. We evaluated 37 patients using EORTC QLQ-C30 (QLQ-30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Six of the cystectomy studies were dedicated to understanding sexual outcomes of surgery in female patients (see Table 3). Eight studies looked at oncological outcomes, quality of life and functional outcomes including sexual function with different types of urinary diversion/reconstruction 11,12,29–35 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of the cystectomy studies were dedicated to understanding sexual outcomes of surgery in female patients (see Table 3). Eight studies looked at oncological outcomes, quality of life and functional outcomes including sexual function with different types of urinary diversion/reconstruction 11,12,29–35 …”
Section: Resultsmentioning
confidence: 99%
“…13 A limited number of studies (n = 7) have examined sexual function in females having cystectomy often centred around a modified surgical approach. 11,12,[29][30][31][32]34,35,65 Outcomes on sexual function varied but generally reported a better outcome with a modified surgical approach. 11,31,33 However, it was also found that this diminished over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,9,10 Moreover, socioeconomic and cultural differences among nations may affect the UD of choice. 11,12 In spite of the abundant number of related studies in developed countries, there has been a striking scarcity of reports from developing countries and especially the Middle East region 13,14 ; urging further investigations. Consequently, the current study was designed and conducted to address this deficiency in the literature.…”
Section: Introductionmentioning
confidence: 99%